We Built It, They Came, Now What? - Anna-Margaret Yarbrough (The University of Alabama, 2022)
Al's Pals is a school-based mentoring program with the purpose of developing and fostering positive relationships between mentors (college volunteers) and mentees (elementary students). Al's Pals was developed in 2010 to meet two goals: 1) provide academic assistance and social development for at-risk elementary students and 2) encourage leadership development for college students through the potential for a) college mentors becoming student leaders, b) developing lesson plans, and c) leading enrichment activities (e.g., teaching Spanish, dance, music, and nutrition education to elementary students). The University of Alabama's Division of Student Affairs and Ferguson Center Student Union embraced these goals, and in fall 2010, decided to house the Al's Pals Program as a way to increase positive college student development while reaching out to the Tuscaloosa community.